2017
DOI: 10.25077/jip.1.1.33-44.2017
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan prinsip DIR/Floortime Meningkatkan Kemampuan Memusatkan Atensi pada Anak dengan ADHD

Abstract: Abstract. Developmental, Individual Differences, Relationship-Based approach (DIR/Floortime) is one of the available interventions focused on increasing the quality of caregiver-child interaction. This study is aimed at investigating the effectiveness of DIR/Floortime to increase the ability to sustain attention on a 4 year-old child with Early Onset Attention-Deficit/Hyperactivity Disorder (ADHD). This is a qualitative research involving two participants, a boy diagnosed with ADHD, and the mother of the boy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…There is only one study in the literature that aims to support sensory, cognitive, and emotional perception in children with ADHD (Larasati et al, 2017), and the results of the current research support the findings of this study. It was observed that the child with a pre-diagnosis of ADHD included in the study had improvements in functional emotional terms after the intervention process, the child's ability to maintain attention improved and the frequency of distraction decreased.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
See 1 more Smart Citation
“…There is only one study in the literature that aims to support sensory, cognitive, and emotional perception in children with ADHD (Larasati et al, 2017), and the results of the current research support the findings of this study. It was observed that the child with a pre-diagnosis of ADHD included in the study had improvements in functional emotional terms after the intervention process, the child's ability to maintain attention improved and the frequency of distraction decreased.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
“…Greenspan and Wieder, 2017). As a result of the study, it was observed that the functional emotional development of the mother and child improved, the child's ability to maintain attention improved and the frequency of distraction decreased (Larasati et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…The increase in motor skills occurs because in the modified ludo game there is sensory input. Optimal motor ability is driven by efficient and accurate sensory intake and optimal processing of sensory input (Larasati et al, 2017). Sensory input obtained in the form of proprioceptive and vestibular input.…”
Section: Discussionmentioning
confidence: 99%
“…Attention disorders or inattention can be seen from the failure of children to give full attention to something, it is easy to switch attention from one thing to another (Larasati et al, 2017). Children with ADD/ADHD also have difficulty concentrating if there are things going on around them, they usually need a quiet, environment to stay focused (Ashori & Bidgoli, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dampak dari inatensi adalah anak sering kali mengalihkan perhatiannya ke berbagai objek lain sesuai dengan apa yang dia dengar, lihat maupun yang dia rasakan. Selain itu, masalah lainnya terletak direndahnya konsentrasi, sulit berfokus pada sesuatu dan sangat mudah teralihkan perhatiannya (Larasati et al, 2017). Tujuan dari studi kasus ini adalah meningkatkan atensi anak ADHD ketika mengerjakan tugas.…”
Section: Pendahuluanunclassified